Changing neighbourhood cohesion under the impact of urban redevelopment: a case study of Guangzhou, China - Liu, Yuqi; Wu, Fulong; Liu, Ye; Li, Zhigang (Urban geography, 2017)
Large-scale urban redevelopment has caused the breakdown of traditional social bonds in Chinese cities. To date, very few studies have attempted to delve into the impact of this urban redevelopment on neighbourhood cohesion. Using data collected from questionnaires conducted in 20 urban villages and 1 urban village redevelopment neighbourhood in Guangzhou, this paper examines the impact of urban village redevelopment on the restructuring of neighbourhood attachment, neighbourly interaction, and community participation-three dimensions of neighbourhood cohesion. Results of a path analysis show that, overall, neighbourhood cohesion declines after redevelopment occurs, and that the sources of neighbourhood cohesion differ between urban villages and the redevelopment neighbourhood. Our findings show that after redevelopment, neighbourhood attachment becomes more influenced by residential satisfaction but less by neighbourly contacts, and community participation becomes less subject to neighbourly interaction and neighbourhood attachment. Such changes occur as a result of the differentiation between social groups and the concurrence of environmental restructuring and demographic reconstruction during the process of urban village redevelopment.